2016
DOI: 10.1371/journal.pone.0156791
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Health Promotion and Mental Health: Three-Year Findings from Partnering Healthy@Work

Abstract: This study aimed to investigate the association between mental health and comprehensive workplace health promotion (WHP) delivered to an entire state public service workforce (~28,000 employees) over a three-year period. Government departments in a state public service were supported to design and deliver a comprehensive, multi-component health promotion program, Healthy@Work, which targeted modifiable health risks including unhealthy lifestyles and stress. Repeated cross-sectional surveys compared self-report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
1
10
0
1
Order By: Relevance
“…Several small improvements in mental health outcomes (stress, depression, and life-satisfaction) were also shown in the present study. These results were generally consistent with other studies that have examined the effect of various worksite interventions on similar outcomes (Chu, Koh, Moy, & Muller-Riemenschneider, 2014; Czabala, Charzynska, & Mroziak, 2011; Jarman et al, 2016). For example, Chu et al (2014) reviewed multiple studies and not only reported an association between worksite physical activity programs and decreased depression symptoms but also noted that “their impact on stress relief is less conclusive.” A review of worksite wellness programs on multiple outcomes by Osilla et al (2012) revealed that three of the four studies reporting mental health outcomes resulted in improvement in these outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Several small improvements in mental health outcomes (stress, depression, and life-satisfaction) were also shown in the present study. These results were generally consistent with other studies that have examined the effect of various worksite interventions on similar outcomes (Chu, Koh, Moy, & Muller-Riemenschneider, 2014; Czabala, Charzynska, & Mroziak, 2011; Jarman et al, 2016). For example, Chu et al (2014) reviewed multiple studies and not only reported an association between worksite physical activity programs and decreased depression symptoms but also noted that “their impact on stress relief is less conclusive.” A review of worksite wellness programs on multiple outcomes by Osilla et al (2012) revealed that three of the four studies reporting mental health outcomes resulted in improvement in these outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…In a previous study, designed as an online survey of workers, lower resilience similarly had a strong association with a higher prevalence of depression for environments with low and high work strain [30]. Given the high prevalence of stress in the corporate environment and mental health diagnoses in this executive population, promoting resilience at workplaces through organizational and individual interventions may be a strategy that helps buffer the negative consequences of workplace stress [6772].…”
Section: Discussionmentioning
confidence: 99%
“…One such study tracked the association between mental health and a comprehensive workplace health promotion program over a three-year period and found that while women's psychological distress decreased over time, this change was only partially attributed to participation in the program. Men's psychological distress did not change over time with participation (Jarman et al, 2016).…”
Section: Combating Mental Health Challenges: Employee Assistance Programsmentioning
confidence: 83%
“…There are a handful of studies that have measured the effectiveness of EAPs in ameliorating employee mental health challenges (Jarman, Martin, Venn, Otahal, Blizzard, Teale, & Sanderson, 2016;Young, 1993). One such study tracked the association between mental health and a comprehensive workplace health promotion program over a three-year period and found that while women's psychological distress decreased over time, this change was only partially attributed to participation in the program.…”
Section: Combating Mental Health Challenges: Employee Assistance Programsmentioning
confidence: 99%
See 1 more Smart Citation